von Economo neurons in autism: A stereologic study of the frontoinsular cortex in children - Santos, Micaela; Uppal, Neha; Butti, Camilla; Wicinski, Bridget; Schmeidler, James; Giannakopoulos, Panteleimon; Heinsen, Helmut; Schmitz, Christoph; Hof, Patrick R. (Brain research, 2011)
The presence of von Economo neurons (VENs) in the frontoinsular cortex (FI) has been linked to a possible role in the integration of bodily feelings, emotional regulation, and goal-directed behaviors. They have also been implicated in fast intuitive evaluation of complex social situations. Several studies reported a decreased number of VENs in neuropsychiatric diseases in which the “embodied” dimension of social cognition is markedly affected. Neuropathological analyses of VENs in patients with autism are few and did not report alterations in VEN numbers. In this study we re-evaluated the possible presence of changes in VEN numbers and their relationship with the diagnosis of autism. Using a stereologic approach we quantified VENs and pyramidal neurons in layer V of FI in postmortem brains of four young patients with autism and three comparably aged controls. We also investigated possible autism-related differences in FI layer V volume. Patients with autism consistently had a significantly higher ratio of VENs to pyramidal neurons ( p = 0.020) than control subjects. This result may reflect the presence of neuronal overgrowth in young patients with autism and may also be related to alterations in migration, cortical lamination, and apoptosis. Higher numbers of VENs in the FI of patients with autism may also underlie a heightened interoception, described in some clinical observations. ►Young patients with autism have a higher ratio of von Economo neurons (VENs) to pyramidal neurons. ►Pyramidal neurons numbers in frontoinsular cortex (FI) do not differ between patients and controls. ►Our results may reflect a postulated neuronal overgrowth in patients with autism. ►Higher number of VENs in FI may underlye a heightened interoception.